A somatic embryogenesis-based system for the production of fluted pumpkin (telfairia occidentalis hook F.) planting materials (2015)
Fluted pumpkin (Telfairia occidentalis Hook. f.) is traditionally propagated by seeds, which have low viability after pod harvest, low percentage germination, and poor root development and often germinate during storage. The competition between use of seeds for consumption and propagation causes scarcity of propagules, necessitating development of more efficient propagation systems. Efficient protocols were developed for the induction of somatic embryos (SEs) and conversion into plantlets using cotyledons from mature zygotic embryos. This study evaluated the effects of 2,4- dichlorophenoxyacetic acid (2,4-D) and kinetin (25 combinations) on the induction of SEs, and of indole-3-acetic acid (IAA), 2,4-D, and kinetin (7 combinations) on conversion of SEs into plantlets. Significantly more SEs (381.7; p<0.01) were obtained on medium with 0.5 mg l−1 2,4-D and 0.1 mg l−1 kinetin than from the other 24 treatments after 4 wk of cotyledon culture. All SEs were obtained through an intermediary callus. For the production of SE-derived plantlets, treatments with 0.01 mg l−1 IAA and 0.02 mg l−1 kinetin resulted in significantly more shoots and roots than other treatments (p<0.001 for each) and gave 100% conversion of SEs to plantlets. The mean numbers of roots and shoots on this treatment were 3.7 and 1.3, respectively, and the mean shoot length was 2.2 cm. The plantlets had broad leaves and good vigor, similar to the parent cultivar. Nearly all plantlets (98–100%) survived acclimatization. The production of SEs from cotyledons and the high rate of conversion into quality plants will allow development of a mass production system for Telfairia planting material to meet the increasing demand for this crop.